Using Basaltic Tuff for Decreasing the Growth Activity of Cyanobacteria - Чебан, Лариса (My University, 2020)
The atricle is devoted to the study of the cultivation of cyanobacteria Microcystis aeruginosa (Kützing) Kützing, Microcystis pulverea (H.C.Wood) Forti. in the presence of basalt tuff. The possibility of using basalt tuff as an adsorbing material for regulating the number of cyanobacteria and preventing toxic “water bloom” in fluid circuits. The study analyzes the change in the biomass amount and the dynamics of the proportion of dead cyanobacteria in response to the presence of basalt tuff in the culture medium. It is noted that the use of basalt tuff leads to a decrease in the growth activity of cultures of Microcystis aeruginosa, Microcystis pulverea, manifested in an increase in the number of dead cells and slowdown the accumulation of cyanobacterial biomass. These effects are the result of a decrease in the amount of available nitrogen in the nutrient medium.
Keywords: M. aeruginosa; M. pulverea; basaltic tuff; cyanobacterial biomass